Experimental and numerical evaluation of steel fibres RC patterns influence on the seismic behaviour of the exterior concrete beam-column connections. (15th July 2022) - Karimi Pour, Arash
Highlights: Five concrete casting patterns were proposed experimentally and numerically under a cyclic load condition; Influence of stirrup spacing, concrete compressive strength, longitudinal rebars ratio on the structural behaviour was also assessed; Cyclic behaviour, maximum lateral resistance and deformation, ductility, efficiency and energy absorption of connection were measured; The ductility and efficiency of the beam-column joints were improved as a result of adding SF in the joint region only. Abstract: Exterior concrete beam-column connections are one of the important parts of the concrete structural frames that play an important role in controlling the seismic behaviour of structures during an earthquake. Providing sufficient ductility for beam-column connections helps to dissipate more energy during a cyclic load and improves the performance of structures. In this study, the cyclic behaviour of exterior concrete beam-column connection was studied experimentally and numerically. To improve the cyclic performance of the connections, steel fibres (SF) were used. A total of 20 exterior concrete beam-column connections were produced and tested under a cyclic load. SF were added at 1% in terms of volume. SF-reinforced concrete was used in four different patterns. In addition, the influence of bent angles for longitudinal reinforcement bar in the connection region was studied: 90° and 135°. Furthermore, the effect of transverse reinforcement on the cyclic behaviour of the connection was studied by providing different spacings in the column: 150 mm and 100 mm. Formerly, a finite element method software, ABAQUS, was used to study the effect of compressive strength of concrete (normal and high-strength), longitudinal rebars ratio and transverse reinforcement spacing in the beam on the behaviour of exterior concrete beam-column connection produced by different SF-reinforced concrete patterns. Evaluation of the maximum lateral load-bearing capacity, drift ratio, maximum displacement, ductility, efficiency and energy absorption of connections were the main aims of this study. The results showed that using SF-reinforced concrete in the connection zone was the best pattern in terms of maximum lateral resistance and deformation of the connections, especially when a 135° bent angle was provided for the longitudinal rebars. In addition, using high-strength concrete led to reducing the ductility and efficiency of connections, particularly when a 90° bent angle were performed for the longitudinal rebar in the connection region.